Inverted structure organic photovoltaic devices employing a low temperature solution processed WO 3 anode buffer layer - Li, Ning; Stubhan, Tobias; Luechinger, Norman A.; Halim, Samuel C.; Matt, Gebhard; Ameri, Tayebeh; Brabec, Christoph (Organic Electronics, 2012)
Solution processing is a convenient method and also the guarantee for low cost and large-scale organic photovoltaic (OPV) production. It was recently suggested that the absorption of OPV devices can be spectrally extended by introducing ternary semiconductor blends, where a second donor with a complementary absorption spectrum is added into the active layer. In this manuscript we demonstrate the successful replacement of poly(3,4- ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) by low temperature solution processed tungsten trioxide (WO ) nanoparticles for inverted OPV devices based on either poly(3-hexylthiophene) (P3HT): phenyl-C61-butyric acid methyl ester (PCBM) or P3HT: poly[2,1,3-benzothiadiazole-4,7-diyl[4,4- bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b′]dithiophene-2,6-diyl]] (Si-PCPDTBT):PCBM active layers. These WO nanoparticles can serve as fully functional anode buffer layers in inverted OPV devices without further treatment, while showing comparable functionality as PEDOT:PSS layers. © 2012 Elsevier B.V. All rights reserved.
Keywords: Anode buffer layer; Inverted structure; Organic photovoltaic; Solution processing; WO 3 nanoparticles